How patients want to engage with their personal health record: a qualitative study. Issue 7 (30th July 2013) - Kerns, John William; Krist, Alexander H; Longo, Daniel R; Kuzel, Anton J; Woolf, Steven H
Abstract : Objective: To assess factors related to use and non-use of a sophisticated interactive preventive health record (IPHR) designed to promote uptake of 18 recommended clinical preventive services; little is known about how patients want to use or be engaged by such advanced information tools. Design: Descriptive and interpretive qualitative analysis of transcripts and field notes from focus groups of the IPHR users and of patients who were invited but did not use the IPHR (non-users). Grounded theory techniques were then applied via an editing approach for key emergent themes. Setting: Primary care patients in eight practices of the Virginia Ambulatory Care Outcomes Research Network (ACORN). Participants: Three focus groups involved a total of 14 IPHR users and two groups of non-users totalled 14 participants. Outcomes/results: For themes identified (relevance, trust and functionality) participants indicated that endorsement and use of the IPHR by their personal clinician was vital. In particular, participants' comments linked the IPHR use to: (1) integrating the IPHR into current care, (2) promoting effective patient–clinician encounters and communication and (3) their confidence in the accuracy, security and privacy of the information. Conclusions: In addition to patients' stated desires for advanced functionality and information accuracy and privacy, successful adoption of the IPHRs by primary care patients depends on such technology's relevance, and on its promotion via integration with primary care practices' processes and the patient–clinician relationship. Accordingly, models of technological success and adoption, when applied to primary care, may need to include the patient–clinician relationship and practice workflow. These findings are important for healthcare providers, the information technology industry and policymakers who share an interest in encouraging patients to use personal health records. Trial Registration: Clinicaltrials.gov identifier: NCT00589173